1982
DOI: 10.1021/ic00135a035
|View full text |Cite
|
Sign up to set email alerts
|

Crystal and molecular structures of bis(4,4',6,6'-tetramethyl-2,2'-bipyridyl)copper(I) perchlorate, bis(4,4',6,6'-tetramethyl-2,2'-bipyridyl)copper(II) diperchlorate, and bis(4,4',6,6'-tetramethyl-2,2'-bipyridyl)copper(II) diperchlorate dihydrate. A search for copper(II) and copper(I) complexes with a common ligand environment

Abstract: Der pseudotetraedrische Club‐Komplex kristallisiert mit Z=4 in der Raiumgrtippe Pben, das Anion ist nicht koordiniert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(40 citation statements)
references
References 10 publications
2
38
0
Order By: Relevance
“…In the case of Cu-phen and in the hypothesis that the coordination number is 5, the breaking of a Cu--O bond could bring the Cu coordination number to 4. As found by others [25], this type of coordination is typical of Cu(I).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…In the case of Cu-phen and in the hypothesis that the coordination number is 5, the breaking of a Cu--O bond could bring the Cu coordination number to 4. As found by others [25], this type of coordination is typical of Cu(I).…”
Section: Resultssupporting
confidence: 83%
“…Finally, a possible explanation to the open problem of the instability of Cu(II) under irradiation can be found in the change in the coordination number of this ion [25].…”
Section: Parmigiani and Deperomentioning
confidence: 99%
“…In 2 this distance is 2.350(5) Å , less than the range of 2.55-2.82 Å [48,49], reported for copper(II) complexes containing coordinated perchlorate. As the steric bulk on carboxamide nitrogens increases from isopropyl (2) to isobutyl (3), the Cu1-O3 distance stretches from 2.350(5) to 2.539(4) Å .…”
mentioning
confidence: 62%
“…In our considerations of the Cu-coordination sphere we refer to analogous compounds as studied by singlecrystal diffraction methods [11][12][13]. In particular, Harrison et al found that Cu complexes of type [Cu(bipy)2C1]2X can exhibit different structures, depending on X, having five-coordinated copper(II) in either with trigonal-bipyramidal or square pyramidal geometry.…”
Section: Structural Model Of R Zr(hi _ X)2cux (Phen)oso(po4)2nh20 (A)mentioning
confidence: 99%
“…It is well known [14] that the pyridine molecule can partially reduce copper, and Burke et al [13] have found two valence states for copper (I and II) in the same type of molecules. Unfortunately the instability of copper under irradiation does not allow any conclusions to be drawn, based on XPS measurements, on its valence state in our compounds.…”
Section: Structural Model Of R Zr(hi _ X)2cux (Phen)oso(po4)2nh20 (A)mentioning
confidence: 99%